2019
DOI: 10.1016/s2213-2600(18)30421-1
|View full text |Cite
|
Sign up to set email alerts
|

Routine monitoring with pleural manometry during therapeutic large-volume thoracentesis to prevent pleural-pressure-related complications: a multicentre, single-blind randomised controlled trial

Abstract: Background: In patients with non-expandable lung, pleural fluid removal can result in excessively negative pleural pressure, associated with chest discomfort, pneumothorax, and reexpansion pulmonary edema. Monitoring pleural pressure during thoracentesis may reduce discomfort and protect against complications. Methods: In this prospective randomized single-blind trial, subjects with large pleural effusions at two academic medical centers were randomly assigned (1:1 ratio) to symptom-guided ("control") versus s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 26 publications
0
45
0
4
Order By: Relevance
“…While conceptually appealing, a recent RCT confirmed that there is no role for routine manometry during large-volume thoracentesis in reducing pain. 45 One explanation for these observations is that the pleural pressure is usually measured intermittently, not continuously; the pleural pressure is measured after the drainage is interrupted so as to measure the true intrapleural pressure rather than the negative pressure generated by suction bottles or gravity. This could lead to periods of "blind time" in between the measurements during which the pleural pressures could drop precipitously without being detected by the proceduralists.…”
Section: Pleural Manometrymentioning
confidence: 99%
“…While conceptually appealing, a recent RCT confirmed that there is no role for routine manometry during large-volume thoracentesis in reducing pain. 45 One explanation for these observations is that the pleural pressure is usually measured intermittently, not continuously; the pleural pressure is measured after the drainage is interrupted so as to measure the true intrapleural pressure rather than the negative pressure generated by suction bottles or gravity. This could lead to periods of "blind time" in between the measurements during which the pleural pressures could drop precipitously without being detected by the proceduralists.…”
Section: Pleural Manometrymentioning
confidence: 99%
“…Several studies addressed whether chest pain is associated with excessive negative Ppl and if it is preventable by routine use of manometry. 36,42,47 Feller-Kopman et al recorded Ppl at end expiration in 169 patients undergoing thoracentesis. 36 Eleven percent of patients developed chest discomfort during thoracentesis.…”
Section: Pleural Pressure Monitoring and Procedural Complicationsmentioning
confidence: 99%
“…Most recently, Lentz et al performed a two-center single blind randomized controlled trial of thoracentesis performed with and without pleural manometry. 47 The primary outcome was development of postprocedure chest discomfort at 5 minutes. No difference was found in patients undergoing thoracentesis guided by manometry versus control.…”
Section: Pleural Pressure Monitoring and Procedural Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…10 A separate multicenter, single-blinded randomized controlled trial using pleural manometry showed that pleural pressure monitoring during large-volume thoracentesis did not alter procedure-related chest discomfort nor change patient-centered outcomes such as breathlessness, volume removed, or time required for the procedure. 11 Together these studies may suggest that thoracentesis performed without using vacuum bottles to drain and without the use of pleural manometry may be reasonable. Additional studies are underway to evaluate gravity versus suction for large-volume thoracentesis (NCT03591952) and gravity versus vacuum-based drainage of indwelling tunneled pleural catheter systems (Newton; NCT03831386).…”
mentioning
confidence: 93%